IMPROVING THE MANAGEMENT OF RISK MINIMIZATION IN THE PROCESS OF CREDITING SMALL AND MEDIUM-SIZED BUSINESS ENTITIES (Scientific Journal of Actuarial Finance and Accounting, 2025)
This paper explores the critical role of risk minimization in the process of crediting small and medium-sized enterprises (SMEs). In light of their importance to the global economy, SMEs often face challenges in accessing financial resources due to the risks perceived by lenders. The study emphasizes the need for improved management strategies that can reduce these risks, thus facilitating better access to credit. It examines various tools and practices such as risk assessment models, credit scoring systems, and collateral management to enhance the creditworthiness of SMEs. By exploring current practices and providing actionable recommendations, the paper aims to offer insights into how financial institutions and policymakers can effectively support the growth of small and medium-sized businesses through improved credit risk management.